Kupatan Traditions in The Religious Practices Of The Community Of Juwet Village in The Concept Of Islamic Traditionalism - Achmad Alfiyan Nor Khoiri 'Abdillah; Mujiasih Mujiasih (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
This research aims to analyze religious practices within the concept of Islamic Traditionalism, focusing on the kupatan tradition in Juwet Village. Islamic Traditionalism as a theoretical foundation highlights the preservation of traditional values and spiritual heritage in the context of Islam that is rooted in everyday life. This research uses qualitative research methods, data obtained through interviews with local people and document analysis related to the focus of research, namely the kupatan tradition and Islamic traditionalism. The results showed that the kupatan tradition in Juwet Village reflects the concept of Islamic Traditionalism in several aspects. First, the tradition of acknowledging one year's mistakes in kupatan is a concrete manifestation of moral and ethical values in Islam. Second, the value of togetherness is reflected in the tradition of exchanging kupat. This practice creates social ties and solidarity among Juwet villagers, in accordance with the principle of togetherness advocated by Islam. Third, the symbol of forgiveness through the use of kupat and lepet at the door of the house creates an atmosphere of peace and tolerance. Kupat at the door of the house is interpreted as a sign of readiness to apologize and receive guests sincerely. This reflects the values of forgiveness and tolerance in Islam that are applied in real life. The importance of tradition in maintaining local cultural values in Juwet Village is in accordance with the concept of Islamic Traditionalism. The implications of the findings of this study can broaden insights into the complexity of the relationship between religious values and local culture and contribute to the preservation of spiritual and cultural heritage in traditional Islamic societies.